Analisis Kerusakan Lapis Permukaan Perkerasan Lentur Menggunakan Metode Pavement Condition Indeks (PCI) (Studi Kasus: Jalan Mustafa Daeng Bunga, Kabupaten Gowa) - Khosasi, Anita; Mursalim; Kalangi, Hendry Tanoto (Jurnal Media Teknik Sipil, 2024)
This study aims to determine the type of road surface damage that occurs on the Mustafa Daeng Bunga Road section using the Pavement Condition Index (PCI) method where this method has a road damage assessment index starting from 0 for failed pavement conditions and 100 for very good pavement conditions so that the review is carried out every 50 meters per segment with a total of 46 segments reviewed with a total road length of 2300 meters. Based on the results of this study, there were only 11 segments of road surface damage from a total of 46 segments, for the final calculation of PCI obtained in each segment of the road damage area in the (STA 1 + 450) perfect road category, (STA 1 + 500) failed road category, (STA 1 + 900 bad road category, (STA 1 + 950) good road category, (STA 2 + 00) sufficient category (STA 2 + 50) good category, in this segment it becomes a priority segment to be repaired immediately (STA 2 + 100) obtained values ranging from 0, 2, 15 and 25 with the category of failed roads, (STA 2 + 150) very good road category, (STA 2 + 200) good road category, (STA 2 + 250) good road category, (STA 2 + 300) very good road condition category, for total damage assessment for 11 segments, this area is included in the poor road category with a PCI value of 37.